2014
DOI: 10.1007/s11065-014-9266-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Healthy Aging, Amnestic Mild Cognitive Impairment, and Alzheimer’s Disease on Recollection and Familiarity: A Meta-Analytic Review

Abstract: It is well established that healthy aging, amnestic Mild Cognitive Impairment (aMCI), and Alzheimer’s Disease (AD) are associated with substantial declines in episodic memory. However, there is still debate as to how two forms of episodic memory – recollection and familiarity – are affected by healthy and pathological aging. To address this issue we conducted a meta-analytic review of the effect sizes reported in studies using remember/know (RK), receiver operating characteristic (ROC) and process dissociation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
201
4
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(257 citation statements)
references
References 148 publications
(263 reference statements)
41
201
4
11
Order By: Relevance
“…This is consistent with previous findings suggesting that aging is associated with decreased recollection and preserved familiarity, and also fits with computational approaches suggesting that older adults are more biased toward memory generalization at the expense of discrimination (Yassa and Stark 2011;Koen and Yonelinas 2014). However, we did not compare our sample to young adults, so it is unknown whether AU adults show similar performance to that of young adults.…”
supporting
confidence: 91%
“…This is consistent with previous findings suggesting that aging is associated with decreased recollection and preserved familiarity, and also fits with computational approaches suggesting that older adults are more biased toward memory generalization at the expense of discrimination (Yassa and Stark 2011;Koen and Yonelinas 2014). However, we did not compare our sample to young adults, so it is unknown whether AU adults show similar performance to that of young adults.…”
supporting
confidence: 91%
“…According to the dual-process theories (e.g. Koen and Yonelinas, 2014;Schoemaker et al, 2014;Yonelinas, 2002), memory for a past experience can be based on a conscious recollection of contextual details from that experience or on an automatic estimation of the strength of that memory trace in the absence of contextual details (a sense of "déjà vu" or familiarity). These models assume that, whereas recollection is impaired in normal aging, familiarity is spared (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Using it as dependent variable in a new ANOVA of 3 groups × 2 repetition conditions, the results revealed that the main effects and the interaction of the two variables were again non-significant. These results show that familiarity seems to be stable throughout a healthy life cycle (e.g., Algarabel et al, 2009;Koen & Yonelinas, 2014;Yonelinas, 2002).…”
Section: Know Judgmentsmentioning
confidence: 63%
“…Of the 60 pairs of stimuli presented on the recognition task, 10 corresponded to the non-repeated intact condition, 10 corresponded to the repeated intact condition, 10 corresponded to the non-repeated rearranged condition (randomly re-matching the stimuli in a different order from the one studied), 10 corresponded to the repeated rearranged condition (randomly re-matching the stimuli in a different order), and 20 corresponded to the new condition. Prior to performing the first recognition task, and following strict RK instructions (Koen & Yonelinas, 2014), the differences between "remembering" and "knowing" were explained to participants (see Kilb & Naveh-Benjamin, 2011, exp. 2), emphasizing that a remember response should only be given if they could communicate a retrieved detail to the experimenter if asked, whereas a know response should be given if they believed the pair had previously been studied, but they were unable to retrieve any specific details.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation